Figurative Language Used in Happy Place by Emily Henry - I Wayan Yogiswaa Mustika; Ida Ayu Made Puspani; Yana Qomariana (EduInovasi: Journal of Basic Educational Studies, 2025)
This undergraduate thesis examines the pragmatic study of the figurative language used in the 2023 fiction novel Happy Place written by Emily Henry. The novel, set against the backdrop of a beautiful seaside town, explores themes of love, friendship, and self-discovery through the lives of Harriet and Wyn. As figurative language is an essential tool for evoking emotions and enriching a story, this research aims to explore how Emily Henry employs various figures of speech, such as metaphor, simile, hyperbole, and personification, to deepen the readers' connection with the characters and their experiences. The study focuses on two primary research inquires: (1) what are the meanings of figurative language found in “Happy Place” Novel by Emily Henry (2) What are the types of the figurative language found in “Happy Place” Novel by Emily Henry. The study aims to identify and describe the language styles in the movie using Perrine's (1982: 61) theory of figurative language, which classifies and explains the meanings of various figures of speech, this study systematically analyzes the textual examples. Furthermore, Abrams and Harpham (2009) theory is utilized to examine the types of figurative language that contain in the dialog or narrative found in the novel. The findings of the study indicate that figurative language in Happy Place serves not only as a stylistic device but also as a fundamental tool for emotional expression and character insight. Through metaphors and other figurative devices, Henry portrays the complexities of human relationships and personal growth, enabling readers to experience the characters’ inner worlds more vividly. The study concludes that figurative language enriches the narrative, deepens the thematic exploration of love and identity, and enhances the novel’s emotional impact.